Characterization of the Brassica napus Flavonol Synthase Gene Family Reveals Bifunctional Flavonol Synthases - Schilbert, Hanna Marie; Schöne, Maximilian; Baier, Thomas; Busche, Mareike; Viehöver, Prisca; Weisshaar, Bernd; Holtgräwe, Daniela (Frontiers in Plant Science, 2021)
Flavonol synthase (FLS) is a key enzyme for the formation of flavonols, which are a subclass of the flavonoids. FLS catalyses the conversion of dihydroflavonols to flavonols. The enzyme belongs to the 2 oxoglutarate dependent dioxygenases (2 ODD) superfamily. We characterized the FLS gene family of Brassica napus that covers 13 genes, based on the genome sequence of the B. napus cultivar Express 617. The goal was to unravel which BnaFLS genes are relevant for seed flavonol accumulation in the amphidiploid species B. napus. Two BnaFLS1 homoelogs were identified and shown to encode bifunctional enzymes. Both exhibit FLS activity as well as flavanone 3 hydroxylase (F3H) activity, which was demonstrated in vivo and in planta. BnaFLS1 1 and 2 are capable of converting flavanones into dihydroflavonols and further into flavonols. Analysis of spatio temporal transcription patterns revealed similar expression profiles of BnaFLS1 genes. Both are mainly expressed in reproductive organs and co expressed with the genes encoding early steps of flavonoid biosynthesis. Our results provide novel insights into flavonol biosynthesis in B. napus and contribute information for breeding targets with the aim to modify the flavonol content in rapeseed.